Revitalisasi Perpustakaan untuk Meningkatkan Minat Literasi Siswa di SDN Cangkringan, Kabupaten Boyolali - Lukad Perdana Sutrisno, Valiant; Hilmy Sagito, Rizaldy; Chandra Pertiwi, Rizkalfi; Aristawati, Luthfi; Rahma Putri, Rahel Fitria; Novitasari, Nadya; Andre Ardiyanto, Geovanni; Aliah, Inayati; Nisa, Zahrotun; Meilia Permata, Hanif Maulidya; Herdiansyah, Hadi (DEDIKASI: Community Service Reports, 2023)
The literacy rate in Indonesia is meager due to the lack of literacy facilities in schools. One of the schools in Indonesia, precisely in Boyolali, namely SDN Cangkringan, has fewer literacy facilities. This activity aims to improve literacy at SDN Cangkringan by revitalizing the library and creating a Reading Corner. The method used in this research is descriptive qualitative, with data sources obtained from observations, documentation, and literature studies carried out before and before library revitalization activities. The results of this activity showed that the library visit rate from students increased by 42%, with active students increasing by 30% after the revitalization was carried out. The existence of a reading corner gives students their own space to read other than that, with this reading corner, students also become more interested in reading because reading facilities are closer.